CMSS (Carboxymethly Sago Starch) as halal thickener for food and beverages industry - Said, Farhan Mohd; Adam, Fatmawati; Nur Syuhada, Asmar; Abdul Rasid, Ruwaida; Zainal Abidin, Sumaiya; Mohd Noor, Nawi; Joharizal, Johari (2019)
The issue of the industry is to diversify the use of Carboxymethly Sago Starch (CMSS) in food products. From the study, researchers managed to formulate CMSS in bakery products. Parameters such as temperature and time of baking play important roles to produce good bread. CMSS is able to be used as a bread improver in the bakery industry.